Character Profile of Pancasila Students in The Film "Sang Prawira" by Onet Adhitia Rizlan and Its Implications in Literature Learning - Anisa, Fitri; Arifin, Zainal (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to describe the intrinsic elements of the film "Sang Prawira", delineate the character of the Pancasila Student Profile in the film, and explore its implications for literature education. This research utilizes a qualitative descriptive method as it aims to describe phenomena in the form of words or language. The subjects of this study are the characters in the film "Sang Prawira", while the objects are the Pancasila Student Profile character and intrinsic elements. The data source for this research is the film "Sang Prawira," and the data consist of dialogues or quotations from conversations in the film. The data collection technique employs documentation methods with note-taking. The data analysis technique in this study consists of four stages: data collection, data reduction, data presentation, and drawing conclusions. The research findings indicate that there are 15 instances of Pancasila Student Profile data present in the film "Sang Prawira". These 15 data points consist of 5 instances of independent characters, 4 instances of collaborative characters, and 6 instances of global diversity characters. It can be concluded that the global diversity characters are the most dominant in the film. It is expected that these characters can be implemented in literature education in schools. The results of the analysis of independent, collaborative, and global diversity characters can be applied in Indonesian literature education, specifically in teaching poetry writing for Grade IX students in junior high school. It is expected that this implementation will foster a creative and innovative learning environment.